Effects of sodium glucose cotransporter 2 inhibitors on risk of dyslipidemia among patients with type 2 diabetes: A systematic review and meta‐analysis of randomized controlled trials. Issue 5 (2nd March 2020) - Li, Dandan; Wu, Tingxi; Wang, Tiansheng; Wei, Hongtao; Wang, Aihua; Tang, Huilin; Song, Yiqing
Abstract: Purpose: Sodium glucose cotransporter 2 (SGLT2) inhibitors are shown to cause small, but significant changes of lipid profiles, we aim to investigate whether such altered lipid profiles can be translated into clinically meaningful changes in dyslipidemia. Methods: PubMed, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for randomized controlled trials (RCTs) that compared SGLT2 inhibitors with placebo or other oral glucose‐lowering drugs in patients with type 2 diabetes mellitus and reported the events of dyslipidemia. A random‐effect meta‐analysis was performed to calculate the pooled estimates with risk ratio (RR) for dyslipidemia risk and weighted mean difference for lipid profiles with their 95% confidential intervals (CIs). Results: Of 2427 studies identified, 15 RCTs involving 7578 patients were included. This meta‐analysis found no association between SGLT2 inhibitors and risk of dyslipidemia (RR: 1.13; 95% CI: 0.91‐1.40). However, SGLT2 inhibitors were significantly associated with increases in total cholesterol by 0.15 mmol/L, low‐density lipoprotein cholesterol by 0.12 mmol/L, and high‐density lipoprotein cholesterol by 0.07 mmol/L while they can significantly decrease triglycerides by −0.12 mmol/L compared to controls. Conclusions: SGLT2 inhibitors were not associated with increased risk of dyslipidemia. Further trials with longitudinal assessment are needed to assess the effect of SGLT2 inhibitors on trajectories of changes of lipid metabolism.